PENGARUH LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT NET PROPERTI INDONESIA - Indah, Indah Pratiwi; Nurul Ilham (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of the work environment and job satisfaction on employee performance at PT. Net Properti Indonesia. The research method used is quantitative with a saturated sampling technique, resulting in a sample of 63 respondents. Data were collected through questionnaires using a Likert scale and analyzed using SPSS version 26, including validity testing, reliability testing, classical assumption tests, simple and multiple linear regression analysis, correlation coefficient analysis, coefficient of determination, and hypothesis testing. The results of the analysis show that the work environment does not have a significant effect on employee performance, as indicated by the simple linear regression equation Y = 36.557 + 0.033X₁, a correlation coefficient of 0.031, and a coefficient of determination of 0.1%, with the hypothesis test result showing t-count0.240 < t-table 1.999. Therefore, H₀ is accepted and H₁ is rejected. Job satisfaction has a significant effect on employee performance, as shown by the regression equation Y = 18.953 + 0.497X₂, a correlation coefficient of 0.556, a coefficient of determination of 30.9%, and the hypothesis test result showing t-count 5.223 > t- table 1.999; thus, H₀ is rejected and H₁ is accepted. Simultaneously, the work environment and job satisfaction have a significant effect on employee performance, as indicated by the multiple regression equation Y = 24.873 − 0.224X₁ + 0.568X₂, a correlation coefficient of 0.589, a coefficient of determination of 34.6%, and an F- count of 15.900 > F-table 3.150 (sig. 0.000 < 0.05).